Recapitulation of Human Embryonic Heartbeat to Promote Differentiation of Hepatic Endoderm to Hepatoblasts - Yoshimoto, Koki; Minier, Nicolas; Yang, Jiandong; Imamura, Satoshi; Stocking, Kaylene; Patel, Janmesh; Terada, Shiho; Hirai, Yoshikazu; Kamei, Ken-ichiro (Frontiers in Bioengineering and Biotechnology, 2020)
Hepatic development requires multiple sequential physicochemical environmental changes in an embryo, and human pluripotent stem cells (hPSCs) allow for the elucidation of this embryonic developmental process. However, the current in vitro methods for hPSC-hepatic differentiation, which employ various biochemical substances, produce hPSC-derived hepatocytes with less functionality than primary hepatocytes, due to a lack of physical stimuli, such as heart beating. Here, we developed a microfluidic platform that recapitulates the beating of a human embryonic heart to improve the functionality of hepatoblasts derived from hepatic endoderm (HE) in vitro. This microfluidic platform facilitates the application of multiple mechanical stretching forces, to mimic heart beating, to cultured hepatic endoderm cells to identify the optimal stimuli. Results show that stimulated HE-derived hepatoblasts increased cytochrome P450 3A (CYP3A) metabolic activity, as well as the expression of hepatoblast functional markers (albumin, cytokeratin 19 and CYP3A7), compared to unstimulated hepatoblasts. This approach of hepatic differentiation from hPSCs with the application of mechanical stimuli will facilitate improved methods for studying human embryonic liver development, as well as accurate pharmacological testing with functional liver cells.